ANALYSIS OF PHARMACIST ATTITUDE TOWARD GOVERNMENT REGULATION NO. 51/2009 CONCERNING PHARMACY PRACTICE (CASE STUDY IN PALEMBANG PHARMACIES) - Rastria Meilanda; Achmad Fudholi; Sumarni Sumarni (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Pharmacist holds authority on professionalism in performing pharmacy work. That authority provides definite legitimacy for pharmacist as a profession in performing her/his function and roles within health domain to achieve pharmacy service standard, particularly in drugs services at pharmacy-store listed in Government Regulation No. 51/2009 concerning pharmacy practice. These function and rule should be indicated within attitude and behave as pharmacist. Attitude and behavior strongly determined the pharmacist’ responsibility and service. The presents research was expected provide a foundation for pharmacist attitude and behavior in implementing PP No. 51/2009. It gives an overview of the readiness of pharmacists in the pharmacy, especially Palembang city  in implementing these regulations so that the objective standard of pharmaceutical care can be achieved. This research is descriptive research, data were gained throught questioner. Pharmacist attitude were classified into three dimensions which named as cognitive, affective and cognation dimensions. Samples were selected by random sampling method by giving questioner titled pharmacist attitude in facing PP No. 51/2009. Collected data were followed by validation and reliability test, then been analyzed to obtain research outcome. Research outcome reveals that most pharmacists in Palembang City has acknowledged and well-understand over PP No.51/2009. They also perceived content and, thus, raise positive attitude and inclined to behave according to the regulation. However, pharmacist who disagree with PP No. 51/2009 since perceives difficult to implement it do not sentenced any sanction both from organization and government, generally this caused by limited knowledge gain by pharmacist.Keywords: Pharmacist, Attitude, PP No. 51/2009